2021
DOI: 10.3390/mi12030282
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Source Add-On EVOM® Device for Real-Time Transepithelial/Endothelial Electrical Resistance Measurements in Multiple Transwell Samples

Abstract: This study provides design of a low-cost and open source add-on device that enhances the functionality of the popular EVOM® instrument for transepithelial/endothelial electrical resistance (TEER) measurement. The original EVOM® instrument is designed for measuring TEER in transwell samples manually using a pair of Ag/AgCl electrodes. The inconsistency in electrode placement, temperature variation, and a typically large (12–24 h) time interval between measurements result in large data variabilities. Thus, to so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Many studies have shown that continuous electrical detection did not significantly influence the electrical properties of the cells. [43][44][45][46][47][48][49] The real-time measurement started after cell seeding for 6 hours. During the entire measurement process, the computer performed segmental fitting on the collected signals in real time by impedance.py.…”
Section: Teer Measurementsmentioning
confidence: 99%
“…Many studies have shown that continuous electrical detection did not significantly influence the electrical properties of the cells. [43][44][45][46][47][48][49] The real-time measurement started after cell seeding for 6 hours. During the entire measurement process, the computer performed segmental fitting on the collected signals in real time by impedance.py.…”
Section: Teer Measurementsmentioning
confidence: 99%
“…21 Early forms of such electrical characterizations were performed using a pair of electrodes, popularly known as "chopstick" electrodes. 22 In this measurement approach, each stick of the electrode pair made of silver/silver chloride (Ag/ AgCl) is placed across a cell culture membrane with adherent epithelial cells. 23 The applied oscillating voltage across the electrodes induces a current that passes through the cells on both transcellular and paracellular paths.…”
Section: Introductionmentioning
confidence: 99%
“…However, no basolateral fluid compartment is present in the cells due to the adherence of the cells to the electrode, which excludes the employment of the ECIS setup in tight junction measurement. , On the other hand, trans-epithelial electrical resistance (TEER)-based measurement correlates the permeability of a cell layer with its electrical resistance. , This form of nondestructive electrical measurement can be utilized to assess the tight junctions where high and low electrical resistance correlates with tight and loose junctions, respectively . Early forms of such electrical characterizations were performed using a pair of electrodes, popularly known as “chopstick” electrodes . In this measurement approach, each stick of the electrode pair made of silver/silver chloride (Ag/AgCl) is placed across a cell culture membrane with adherent epithelial cells .…”
Section: Introductionmentioning
confidence: 99%